Rabies virus in Molossus molossus (Chiroptera: Molossidae) in the State of Pernambuco, Northeastern Brazil - Silva,Luiz Augustinho Menezes da (2011)
Rabies virus was detected in bats (Molossus molossus) from an urban area in the City of Recife, State of Pernambuco, Brazil. Four individuals were found during the day in visible, non-habitual places, lying on the ground, but still alive. No contact occurred with people or animals. Of these, only two were identified; it was not possible to identify two specimens, since they were incinerated prior to identification. Diagnosis was positive by direct immunofluorescence and intracerebral inoculation in mice. This study presents the first instance in which the virus was detected in insectivorous bats in the State of Pernambuco.